НАЦИОНАЛЬНАЯ ИДЕОЛОГИЯ НЕЗАВИСИМОГО КАЗАХСТАНА «МƏҢГІЛІК ЕЛ» - Сатыбалдина, Р.А. (My University, 2019)
Аннотация В статье рассматривается роль национальной идеи в становлении и развитии госу- дарства. Национальная идеология – это часть духовной и культурной жизни нации, она предопределяет жизненную правдивость и особенность национальной жизнедеятельности общества. Особое внимание уделено анализу идеи «Мəңгілік ел» в жизни казахстанского общества. Abstract The article discusses the role of the national idea in the formation and development of the state. National ideology is a part of the spiritual and cultural life of a nation, it predetermines the vital truthfulness and peculiarity of the national activity of the society. Particular attention is paid to the analysis of the idea of « Mangilik El » in the life of Kazakhstan society.
National ideology of independent Kazakhstan «Mangilik el»
Keywords: «Мəңгілік Ел»; независимый Казахстан; образование; перспективы; модернизация; национальная идея; «Mangilik El»; independent Kazakhstan; education; prospects; modernization; national idea